Aplikasi Pupuk Organik dan Residunya untuk Produksi Kedelai Panen Muda - Maya Melati; Ai Asiah; Devi Rianawati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
The study was conducted to investigate the effect of different organic manures and their residues on the production of vegetable soybean. The experiments were conducted at IPB Research Station in Cikarawang, Darmaga, Bogor; in September 2005 to May 2006 and August to December 2006. Single or combination of organic manures (chicken manure, green manure, composts and rice hull ash) was applied in the first experiment; while effect of the residues were investigated in the second experiment. The treatments were arranged in a Completely Randomized Design with 3 replications. Single or the combination of organic manures and the residues did not result in significant difference in all agronomic characters, but chicken manure tended to be the best organic manure when it was used as single application. From these experiments, the highest number of filled pod was 56/plant and the highest fresh weight of filled pod was 48 g/plant from the actual population of + 200.000 plants/ha. Additional result from the experiment was that rice hull ash significantly reduced the intensity of plant pest by 75% from that of control. Key words: vegetable soybean, organic fertilizers, residual effects